2007
DOI: 10.4028/www.scientific.net/msf.534-536.1401
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Nanostructured Aluminum Consolidated by SPS

Abstract: Nanostructured aluminum powders were obtained by means of planetary ball milling with methanol as the Process Control Agent (PCA). The behavior, during milling, was considered measuring the microhardness and grain size at different milling times. Bulk near-full density samples were sintered using the Spark Plasma Sintering technology with different schedules: temperature of 500°C and 550°C, pressure of 30 MPa and 60 MPa and different modes of applying the pressure were changed in order to understand the behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Given that polonium has a vaporisation temperature that is lower than the predicted SPS sintering temperature of Tungsten ($1500°C), production of a consolidated polonium-tungsten matrix may be challenging. Alternatively a polonium-aluminium substitute matrix could be produced since aluminium has been consolidated using an SPS furnace at around 500-550°C by Zadra et al [44] given that this is less than the vaporisation temperature of polonium. Such a consolidation would depend upon the existing GPHS module internal aeroshell to ensure safe re-entry of the cermet into the atmosphere but is likely to be able to maintain capture of the polonium loading.…”
Section: System Radiation Environment Modelling and Shielding Criteriamentioning
confidence: 99%
“…Given that polonium has a vaporisation temperature that is lower than the predicted SPS sintering temperature of Tungsten ($1500°C), production of a consolidated polonium-tungsten matrix may be challenging. Alternatively a polonium-aluminium substitute matrix could be produced since aluminium has been consolidated using an SPS furnace at around 500-550°C by Zadra et al [44] given that this is less than the vaporisation temperature of polonium. Such a consolidation would depend upon the existing GPHS module internal aeroshell to ensure safe re-entry of the cermet into the atmosphere but is likely to be able to maintain capture of the polonium loading.…”
Section: System Radiation Environment Modelling and Shielding Criteriamentioning
confidence: 99%
“…Bulk NC/UFG Al samples have been fabricated by SPS of NC Al powders produced by high-energy mechanical milling (HEMM) [4][5][6][7][8]. It was found that the grain growth was severely inhibited during SPS with the minimum grain size being down to 90 nm and its relative density being close to 100% [5]. Such NC/UFG Al samples can sustain strong grain boundary strengthening according to the Hall-Petch relationship [4].…”
Section: Introductionmentioning
confidence: 99%
“…Powder consolidation was done by SPS, since this requires lower temperatures and much shorter times than conventional hot pressing techniques ( Ref 15,16). These characteristics make SPS particularly suitable to the processing of nanostructured powders ( Ref 3,7,8,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%